PENANAMAN NILAI-MORAL PADA ANAK DALAM KELUARGA NELAYAN DUKUH TANJUNGSARI - Wibawa, Angga Cahya; Suyahmo, Suyahmo; Setiajid, Setiajid (Unnes Civic Education Journal, 2015)
The cultivation of moral values performed in the family fishermen is a form of informal education. The purpose of this study was to explore the implementation of the moral values cultivation in children in a family of fishermen, who were most responsible, what are the factors that affect and what are the barriers experienced in the cultivation of moral values in children in a family of fishermen. This study used a qualitative approach. Data was collected through interviews, observation and documentation. The results showed that: 1) cultivation of moral values in children in a family of fishermen in Tanjungsari Sugihwaras Pemalang Pemalang has been good enough. 2) Parties involved in cultivation of moral values in children in a family of fishermen are all members of a family of fishermen and fishing families from the nearest person. 3) Factors that affect the cultivation of moral values in children in a family of fishermen are environmental factors because the social environment will greatly affect children’s behavior. 4) Barriers to the cultivation of moral values in Tanjungsari is the low motivation from within the child’s own fishermen, besides other obstacles in the cultivation of moral values such as the rapid transfer of global knowledge, globalization and the development of sophisticated technology.